Algebraic thinking in early childhood education: teaching strategies to promote patterning skills (Edma 0-6: Educación Matemática en la Infancia, 2023)
The aim of this article is to shed light on the limited curriculum treatment of repeating patterns. Teaching strategies are presented to promote patterning skills in early childhood education, as they form an essential basis for developing algebraic thinking. To this end, the article is structured in two parts: 1) the development of algebraic thinking and its connection with patterns is theoretically based; 2) various tasks are shown to exemplify working with repeating patterns, in which different skills are used: a) copying; b) interpolating; c) extending; d) abstracting or translating; e) recognising the unit of repetition; and f) creating. Finally, guidelines are offered to teachers for approaching the work on patterns in the classroom, through a longitudinal itinerary on patterning skills. It is concluded that it is necessary to design dynamic proposals framed in multimodal contexts that address a diversity of tasks on repetition patterns.
Keywords: Early Childhood Education; Algebraic thinking; Repeating patterns; Patterning skills